Empower the consumer!: Energy-related financial literacy and its socioeconomic determinants - Julia Blasch; Annina Angelina Boogen; Claudio Daminato; Massimo Filippini (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
To be aware of the potential for energy savings in their homes, individuals need specific energy-related and financial knowledge. In addition, they also need the cognitive skills to apply this knowledge, for example when it comes to the calculation of the lifetime cost of household appliances or energy-efficient renovations. This set of knowledge and skills is related to two literacy concepts, i.e. energy and financial literacy. In this paper, we propose a new concept of literacy that we call "energy-related financial literacy". Further, we present information on the level of financial literacy as well as on the level of energy-related financial literacy for a sample of European households. In the empirical part of the paper we estimate several ordered probit models in order to analyse the determinants of the level of energy-related financial literacy, with a particular interest to understanding the role of gender. Our results show that the level of energy-related financial literacy is relatively low and heterogeneous across the European countries. Moreover, the results confirm previous findings about the gender gap in financial literacy, with males being associated with higher levels of the index. We also identify such a gender gap for energy-related financial literacy.
Keywords: Q52; Q54; O10; 330; Energy literacy; financial literacy; energy-related financial literacy; consumer awareness; energy knowledge